Study on Academic Achievement of Students: Factors influencing academic achievement: A comprehensive study (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Academic performance or academic achievement is the extent to which a student has achieved short or long-term educational goals. Completion of educational benchmarks such as secondary school diplomas and bachelor's degrees represent academic achievement.Academic achievement is generally measured through examinations or continuous assessments but there is no general agreement on how it is evaluated, best way or which aspects are most important—procedural knowledge such as skills or declarative knowledge such as facts. Additionally, there are inconclusive results over which individual factors predict academic performance, elements like test anxiety, environment, motivation, and emotions require consideration while developing models of school achievement.